Pengaruh Harga Dan Inflasi Terhadap Ekspor Pada Produk Kopi Ke Amerika Serikat - Afriliyanti; Ade Firmansyah; Nur Fitri Rahmawati (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. Coffee is one of Indonesia's main export commodities. The United States is the largest market for coffee exports. This study aims to analyze the effect of price and inflation on exports of coffee products to the United States. This research is a type of explanatory research with a quantitative approach. The variables used in this study are price, inflation and exports. The data used is multiple linear regression analysis with time series data in 2015-2023. Secondary data obtained from the Central Statistics Agency (BPS) and the International Coffee Organization (ICO). The results showed that price has a negative and significant effect on exports of coffee products, while inflation also has the same effect, which is negative and significant. Recommendations for future research include analyzing other factors such as trade policies and climatic conditions that may affect Indonesian coffee exports. Keywords: Export, Price, Inflation